Pembentukan Persuasif Dalam Struktur Naratif Pada Iklan Gopay Indonesia Versi Bumbu Rahasia Dari Bu Sisca Yang Bikin #Lebihenak - Alfiani Kristiana Dewi; Handriyotopo Handriyotopo (ISI Press Institut Seni Indonesia Surakarta, 2021)
The concept of an advertisement aimed at modern society can no longer rely solely on the description of a product. Because basically people can find their own info from a product using their smartphone. Therefore, an advertisement must be designed in such a way that it really attracts potential consumers. Persuasive messages need to be packaged well in order to achieve the target to influence consumers to use the company's products. The research